A161: Novel 3‐Dimensional Explant Method Facilitates the Study of Lymphocyte Populations in the Synovium and Reveals a Large Population of Resident Memory T cells in Rheumatoid Arthritis. Issue 11 (March 2014) - Henderson, Lauren A.; King, Sandra L.; Ameri, Sarah; Martin, Scott D.; Simmons, Barry P.; Nigrovic, Peter A.; Fuhlbrigge, Robert C.
Abstract : Background/Purpose: Traditionally, immunologic memory was thought to be maintained by populations of central (TCM) and effector (TEM) memory lymphocytes that circulate in the blood and lymphatics, only temporarily extravagating into peripheral tissue to execute immunologic responses. Recently, this theory of adaptive memory has been challenged by the discovery of long‐lived and stable populations of tissue‐resident memory T cells (TRM). While TRM have been implicated in the pathogenesis of skin, intestinal, and lung inflammatory diseases, little information is available about TRM in synovium. The study of TRM in arthritis has been impaired by the scarcity of synovium samples coupled with the meager yield of lymphocytes from this tissue using conventional tissue digestion protocols. We have employed novel culturing techniques, previously used to examine TRM in skin, to further characterize TRM in inflammatory arthritis. Methods: Discard synovium samples were collected from patients with rheumatoid arthritis (RA) who were undergoing joint replacement surgery. A 3‐dimensional explant method was used to isolated synovial T cells. Synovial tissue was cut into pieces with scissors, loaded on titanium matrices, and cultured in 24 well plates with T cell media enriched with IL‐2, 15. After 3 weeks, T cells were harvested. Cell surface markers were studied with flow cytometry. Intracellular cytokine expression was assessed by flow cytometry after T cells were stimulated, fixed, and permeabilized, while Foxp3 expression was evaluated following fixation and permeabilization. Results: Seven RA synovial samples were obtained from 5 women and 2 men. All patients were receiving immunomodulatory medications (prednisone n = 5, methotrexate n = 2, tumor necrosis factor inhibitors n = 1). Synovial samples were small, ranging from 0.5 mm2 to 2 mm2; yet, a substantial number of mononuclear cells were harvested (mean: 7.5 × 106). The isolated lymphocytes were phenotypically similar to prior published reports of synovial T cell populations. The majority of CD3 + lymphocytes were CD4 + (Mean ± SEM: 73.5 ± 7.1%) compared to CD8+ cells (25.5 ± 7.3%). In the CD4+ subset, interferon gamma expression was common (39.5 ± 9.0%), IL‐17 + expression was rare (range: 0.1 to 3.4%), and T regulatory cells (CD4 + CD25 + Foxp3 + ) were present (8.9 ± 3.2%). A memory phenotype characterized by CD45RO + expression predominated in both CD4 + (94.5 ± 2.4%) and CD8 + (78.0 ± 6.8%) lymphocytes. A TRM population that lacked the TCM cell surface markers CCR7 + and CD62L + was identified in CD4 + (47.5 + 10.6%) and CD8 + (36.8 ± 8.1%) cells. Conclusion: The 3‐dimensional explant culturing method is a novel tool, which can be employed to study lymphocytes that are resident in synovium. We confirmed that the T cells isolated through this technique were phenotypically similar to populations of RA synovial lymphocytes previously assessed by immunohistochemistry and tissue digestion. A population of TRM was identified in all synovial samples, suggesting these T cells may be important in the pathogenesis of inflammatory arthritis, though further study of this population is needed.